2014
DOI: 10.1002/cssc.201400133
|View full text |Cite
|
Sign up to set email alerts
|

Equimolar Carbon Absorption by Potassium Phthalimide and In Situ Catalytic Conversion Under Mild Conditions

Abstract: Potassium phthalimide, with weak basicity, is an excellent absorbent for rapid carbon dioxide capture with almost equimolar absorption. This process is assumed to proceed through the potassium carbamate formation pathway, as supported by NMR spectroscopy, an in situ FTIR study, and computational calculations. Both the basicity and nucleophilicity of phthalimide salts have a crucial effect on the capture process. Furthermore, the captured carbon dioxide could more easily be converted in situ into value-added ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 83 publications
1
32
0
Order By: Relevance
“…Metal carbamates for CO 2 capture. The formation of metal carbamates from gaseous CO 2 and a metal amine complex has direct implications in the CO 2 capture and storage (CCS) technology [373][374][375][376][377]. In particular, amine-functionalized metal organic frameworks play an important role in the development of new solid sorbent materials [378].…”
Section: Other Applicationsmentioning
confidence: 99%
“…Metal carbamates for CO 2 capture. The formation of metal carbamates from gaseous CO 2 and a metal amine complex has direct implications in the CO 2 capture and storage (CCS) technology [373][374][375][376][377]. In particular, amine-functionalized metal organic frameworks play an important role in the development of new solid sorbent materials [378].…”
Section: Other Applicationsmentioning
confidence: 99%
“…However, the peaks at 1619 and 1588 cm À1 , which were assigned to the ve-membered cyclic imide anion of [P 66614 ][Ph-Suc], was blue shied to 1769 and 1720 cm À1 , respectively, suggesting the interaction between CO 2 and N atom in the anion. 34 Based on the above solubility data and the spectroscopic investigation of the ILs before and aer CO 2 S1, † respectively, where the negatively charged N atom in the anions interacted with CO 2 and formed the complexes.…”
Section: Chemical Absorption Mechanism Of Co 2 In the Ionic Liquidsmentioning
confidence: 98%
“…4. 34 The NMR and FT-IR spectra of [P 66614 ][Ph-Suc] before and aer the absorption of CO 2 were showed in Fig. S1.…”
Section: Chemical Absorption Mechanism Of Co 2 In the Ionic Liquidsmentioning
confidence: 99%
“…However, recent studies of the cation effects on the interactions between Lewis base and CO 2 have displayed a different picture. In 2014, He and Dai groups reported that the introduction of lithium or potassium into organic bases improved their CO 2 uptake to nearly equal molar level, a result of forming stable zwitterionic metal carbamate adducts with CO 2 being sandwiched in the middle 17 , 18 . In parallel, theoretical works by Neaton group proved that the interactions between NHCs and CO 2 were strengthened by the positively charged metal centers in NHC-grafted MOFs 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%